Rāma: Helt, gud og politisk symbol - Rasmus Reinvang (Religionsvidenskabeligt Tidsskrift, 2000)
The article “Rāma: Hero, God and Political Symbol” outlines three different ways in which the Rāma-figure has been used in Indian history. As a basis, hermeneutical problems related to the critical interpretation of the Rāmāyana are briefly discussed, and the main story of the epic is outlined. In the core parts of the Rāmāyana epic, Rāma can still be recognised as representing the ethos of the warrior-class (ksatrīya-varna). The Rāma of this historical phase, approximately covering the era between 400 B.C. and the Gupta era (320-500 A.D.), incarnates the dharma of the ksatrīya; which implies protection of the just, combat against the powers of chaos, and the maintaining of the norms and the social divisions of society. When the classical Rāmāyana finds its basic form during the Gupta period, under the hands of Vaisnavite Brahmins, Rāma is extolled as being an incarnation of the supreme god Visnu. As such, Rāma is God, having incarnated on earth to save mankind from evil and the universe from the powers of chaos. Brahminical notions of purity are now considered essential to the Rāma-figure, with the effect that the conclusion of the original story has to be rewritten so that Rāma does not take his abducted - and thus defiled - wife Sītā back after she has been liberated from the evil rāksasa Rāvana. The ksatrīya-Rāma has thus been replaced with a vaisnava-Rāma, a Rāma incarnating a different set of values. As a parallel to this historical development, the article proceeds to outline how, during the last twenty years, Rāma has become a symbol of a new Hindu-nationalistic consciousness. In this context, Rāma is imagined as a warrior ready to fight for the assertion of “hinduness” (hindutva), in opposition to what is considered a century’s old suppression carried out by Muslim rulers, the British Raj and the independent, secular Indian state. Political campaigns and the conflict around the Babri-masjid in Ayodhyā, are highlighted in order to show how Rāma, through the stratagems of the Hindu nationalistic movement, has recently emerged as a symbol of an aggressive Hindu consciousness. The article stresses that the main presuppositions for the Hindu nationalistic use of Rāma are to be found in the political culture of modern India, which takes its outset in forms of organisation and concepts of political thought imported by the British. There is thus nothing essentially and eternally “Indian” about the present Hindu nationalism. Finally, the article notes that the very fact that an ancient Indian symbol in the Hindu nationalistic context is revitalised and transformed to fit the circumstances of the present, reflects the inherent power of what we generally call “Hinduism” (a modern term originally coined by European scholars). As was the case when the original warrior-hero Rāma in the Gupta era was made into an incarnation of the supreme God, due to the mode of the religious sentiments of the time and the interest of certain classes, Rāma has lately become a political symbol, due to the mode of the political sentiments in the India of the present and the interests of certain classes. Again, the complex blend of change and continuity, so characteristic of “Hinduism”, leaps to mind.